A lateral flow immunochromatographic strip test for rapid detection of hexoestrol in fish samples. Issue 8 (29th August 2018) - Yang, Xingdong; Sun, Zhongke; Tian, Fengshou; Jia, Guochao; Yang, Jifei; Hu, Xiaofei
Abstract : A lateral flow immunochromatographic strip test was developed for rapid and sensitive on-site detection of hexoestrol (HES) residues in fish samples with colloidal gold labelling of the anti-HES monoclonal antibody. The strip is composed of a sample pad, a conjugate reagent pad, an absorbent pad and a test membrane containing a control line and a test line. The sensitivity (half inhibitory concentration, IC50 ) of the strip in the detection of fish extract samples was confirmed to be 1.86 µg kg −1, and the limit of detection value was 0.62 µg kg −1 . For intra-assay and inter-assay reproducibility, recoveries of HES-spiked samples ranged from 86.3% to 92.3% and 85.8% to 93.4%, coefficients of variation were 2.91–4.64% and 4.24–5.17%, respectively. High-performance liquid chromatography was employed to confirm the performance of the strip. The strip test takes less than 10 min, and thus provides a repaid method for on-site detection of HES residues.